Improving Student’s Critical Thinking Through Recitation Method in Social Studies Classroom - Widiyanti Widiyanti; Aman Aman; Primanisa Azizah; Rusyda Rahman (Universitas Negeri Yogyakarta, 2026)
Developing students' critical thinking has become an important objective of social studies education, yet classroom instruction often provides limited opportunities for students to engage in inquiry, collaborative reasoning, and evidence-based argumentation. This study explored how structured recitation activities fostered students' critical thinking during social studies learning through a qualitative classroom inquiry. The study involved eight junior high school students and employed classroom observations, semi-structured interviews, students' learning artifacts, and classroom documentation as primary data sources. Data were analyzed using the interactive analysis model of Miles, Huberman, and Saldaña, involving data condensation, data display, and conclusion drawing. The findings revealed four interconnected themes characterizing the development of students' critical thinking: (1) developing collaborative learning engagement, (2) building learning confidence through peer support, (3) developing evidence-based critical thinking, and (4) strengthening independent inquiry through structured recitation activities. Students gradually shifted from passive participation toward active engagement by collaboratively seeking information, discussing ideas, constructing arguments, and defending their conclusions using evidence. These qualitative findings were supported by improvements in students' critical thinking achievement throughout the learning process. The study concludes that structured recitation activities provide meaningful learning experiences that extend beyond improving academic achievement by promoting collaboration, learner autonomy, analytical reasoning, and reflective participation. The findings offer practical implications for social studies teachers seeking to design more student-centered learning environments that effectively foster critical thinking.